Hubungan Supervisi Akademik Kepala Madrasah dengan Peningkatan Mutu Pembelajaran di Madrasah Tsanawiyah Jamiatul Huda Kabupaten Bekasi - Ibrahim, Tatang; Robiah, Siti (Bestari, 2020)
The essence of education is a learning process. There is no quality education without quality learning. Changes in the system of management, both from the point of view of educators and educational personnel, must have clear supervision. Therefore, in order to improve the quality of education in madrasah, the government, in this case the Ministry of National Education, is developing various programs which are expected to improve the quality of learning, especially through supervision activities. This study aims to determine whether there is a positive and significant relationship between the academic supervision of the head of madrasah and the improvement of the quality of learning at Madrasah Tsanawiyah Jamiatul Huda Bekasi district. This research is based on the idea that one of the ways to improve the quality of education is by increasing the quality of learning. In this case the learning process is an important component in determining the quality of education. besides teachers and students who are in the implementation of the learning process. The activities of the principal of madrasah in supervising, guiding, fostering teachers in the learning process use academic supervision. For this reason, the research was conducted to determine whether there was a relationship between the academic supervision of the head of the madrasah and the improvement of the quality of learning at Madrasah Tsanawiyah Jamiatul Huda, Bekasi district. The approach used in this study is a quantitative approach, correlational type and uses a simple linear regression method. The population is all teacher councils at Madrasah Tsanawiyah Jamiatul Huda Bekasi Regency and as many as 28 people. Research data using the SPSS 26 for windows program. The results of this study indicate that the academic supervision of the head of madrasah has a positive and significant relationship with the improvement of the quality of learning at Madrasah Tsanawiyah Jamiatul Huda Bekasi district. Based on the results of the research, the following suggestions can be made: (1) Madrasah supervisors and madrasah principals are expected to supervise not only matters of an administrative nature, but prioritizes supervision in the academic field, so as to improve the innovative performance of teachers who In the end, improve the quality of education, (2) maximize classroom observations or class assessments, so that the head of madrasah is aware of teacher teaching developments and teacher constraints and is able to provide solutions in improving the learning process.